A Familial Hypokalemic Periodic Paralysis : A Case Report - Rizaldy Taslim Pinzon; Larasati, Yutta (Acta Neurologica Indonesia, 2024)
Hypokalemic periodic paralysis is characterized by recurrent attacks of skeletal muscle weakness with related hypokalaemia which is a rare genetic disorder. There might be a limited weakness for some groups of muscle, or it might appear as severe muscle paralysis. The muscle cells increase the uptake of potassium, hence the decreasing of potassium’s mechanism. The case of a clinically diagnosis familial hypokalaemia periodic paralysis in a 9-year-old boy that we report is established in this proband that settle the consensus diagnosis criteria for primary hypokalaemia periodic paralysis according to previous review that’s been published. Key words: paralysis-hypokalemia-periodic-familial.